PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Muhammad Nur Fitra; Mursalim Mursalim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
Aim of the research to investigate the relation between Intellectual Capital (IC) which based on company resources (is Capital Employee, Human Capital, and Structural Capital) against to financial performance analyze through profitability rasio ROA (Return on Asset). The population in this research consist of 43 Banks. Sample determination of this research based on certain characteristics was based on publication of minimum financial statement for 4 years (2013-2016), listed on BEI for the last 4 years and total assets with value above 100 trillion rupiah. The data is processed by interpretation bank financial statement based on the VIAC formula (Pulic, 2000). The data were analyzed by using multiple regression through SPSS program vers. 21. The result of this research was indicate that Human Capital, Structural Capital and Capital Employee as simultaneously have significant impression to Return On Asset valueable. As for partially the Capital Employee is the only things from the third variabel dependent was have an signficant impression to Return On Asset Value in Banking Companies.